Growth and characterization of Ta-doped Ga2O3 films deposited by magnetron sputtering. (1st November 2021) - Shang, Yi; Tang, Ke; Chen, Zhuorui; Zhang, Zhiluo; Deng, Jie; Hu, Yan; Gu, Keyun; Cao, Meng; Wang, Linjun; Huang, Jian
Abstract: In recent years, Ga2 O3 has attracted extensive attention at home and abroad due to its excellent properties. In this paper, Ta-doped Ga2 O3 films were grown on quartz substrates by magnetron sputtering technique. Effects of substrate temperature and seed layer on the performance of the films were investigated. The results showed that all films had uniform, smooth surface morphology and better transparency (>85%) in the wavelength region of 300–800 nm. Hall effect measurement revealed low resistivity of 0.089 Ω cm and high carrier concentration of 2.4 × 10 19 cm −3 for the Ta-doped Ga2 O3 film grown with seed layer. XPS spectra demonstrated that Ta was incorporated into the Ga2 O3 films and Ta 5+ ions were obtained.